Diagnostic challenges of gastrointestinal stromal tumour during transurethral resection of the prostate: A case report - Anandia Putriyuni; Yevri Zulfiqar; Santy Saberko; Lila Indrati (Faculty of Medicine, Universitas Islam Indonesia, 2023)
Mesenchymal prostate tumours are relatively rare compared to epithelial tumours. To diagnose mesenchymal tumours on transurethral resection of the prostate (TURP) specimen, doctors have to consider a few differential diagnoses, including gastrointestinal stromal tumour (GISTs). We reported a 63 years-old male patient, presented with urinary retention in one week. Based on an initial scan of the abdomen, a large lobulated mass in the pelvic cavity from the prostate pushed up the urinary bladder. Histopathologic examination demonstrated cellular spindle cell neoplastic proliferation, a moderate degree of atypia, and a mitotic count of >5 per 50 high-power fields (HPFs) with a fascicular growth pattern. Immunohistochemically, the tumour had positive expression for CD117 (c-KIT), CD34, and discovered on Gist-1 (DOG-1), while smooth muscle actin (SMA) and S-100 were negative. The pathological report was consistent with a high-risk group of GISTs in the prostate. Subsequent imaging revealed that the tumour mass was centrally located between the rectum and prostate, infiltrating bladder and liver metastases. Comprehensive differential diagnoses of mesenchymal tumours involving the prostate are necessary because of the inadequacy of specific clinical signs, symptoms, and unexpected location. Diagnoses of GISTs was performed based on spindle cell pattern and the positive immunohistochemistry expression for CD117, CD34, and DOG-1. The tumour mass involved in the prostate with spindled morphology should be considered as a GIST, assisted with appropriate immunohistochemistry marker panel. It is a challenge to diagnose the GIST particularly involving the prostate.